2018
DOI: 10.1080/0092623x.2017.1405303
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Experiences in Transgender People: The Role of Desire for Gender-Confirming Interventions, Psychological Well-Being, and Body Satisfaction

Abstract: We examined the role of gender-confirming treatment (GCT; i.e., hormonal treatment and genital surgery), psychological well-being, and body satisfaction in the sexual feelings and behaviors of transgender adults. A survey was conducted among a nonclinical sample of 325 male-to-female (MtF) and 251 female-to-male (FtM) Dutch adults (17-76 years, M = 41.87), divided into those with no GCT desire, those who desired (more) GCT, and those who completed GCT. Findings indicated that whereas GCT may positively affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 24 publications
5
43
1
Order By: Relevance
“…An important area of improvement includes one's gender affirmation. A finding that confirms other studies (Nikkelen & Kreukels, 2018;van de Grift, Elaut et al, 2017) observing positive associations among gender affirmation, body satisfaction and sexual outcomes. Also, participants experienced increased sexual initiative and sexual pleasure.…”
supporting
confidence: 91%
“…An important area of improvement includes one's gender affirmation. A finding that confirms other studies (Nikkelen & Kreukels, 2018;van de Grift, Elaut et al, 2017) observing positive associations among gender affirmation, body satisfaction and sexual outcomes. Also, participants experienced increased sexual initiative and sexual pleasure.…”
supporting
confidence: 91%
“…Trans women (MtF) who receive cross-sex hormone treatment usually experience a decrease in testosterone, whereas trans men (FtM) generally face an increase in testosterone levels. GAS may have less direct effects on sexual drive, whereas it seems to be more linked to general body satisfaction, personal sexual identity recognition, and sexual pleasure [24]. A recent online survey [23•] revealed that the most frequent sexual problems experienced by trans women and men in HT were desire and orgasm difficulties.…”
Section: Transgender Women and Menmentioning
confidence: 99%
“…Compared with trans people (both men and women) under HT only, trans people after GAS seemed to report low sexual desire, aversion, and arousal difficulties less often. A large Dutch study [24] considered 325 MtF and 251 FtM divided in 3 groups: no desire for treatment (NTD), wanting a treatment (UTD), and treatment fulfilled (FTD). For MtF, no difference was found regarding partnered sexual activity frequency among the 3 groups, while masturbation was higher in NTD than the other two groups.…”
Section: Transgender Women and Menmentioning
confidence: 99%
“…Several limitations are noteworthy. First, prior research has considered gender affirmation treatment desire in relation to sexual functioning, 10 yet the present study did not evaluate whether TM participants desired body modifications or had unfulfilled gender affirmation desires. Second, this sample is restricted to TM adults eligible to undergo cervical cancer screening; thus, this study was unable to assess differences in sexual functioning in those who have and have not had genital surgery.…”
Section: Discussionmentioning
confidence: 92%